Imagine it forward :Courage,creativity and the power of change - Comstock, Beth (Virgin, 2018)
"From one of today's foremost innovation leaders, an inspiring and practical guide to mastering change in the face of relentless uncertainty. The world will never be slower than it is right now, says Beth Comstock, the former Vice Chair and head of marketing and innovation at GE. But confronting the relentless pace of change is hard. Employees get downsized; companies find themselves disrupted as challengers steal away customers. To thrive in today's world, every one of us has to become a change-maker. In Imagine It Forward, Comstock shares lessons from a thirty year career as the change-maker in chief, on spotting trends and driving innovation. In a candid and deeply personal narrative, Beth describes her successes and failures from the front lines of business, across industries ranging from media to health, energy to manufacturing, finance to the Industrial Internet. As the woman who spearheaded Ecomagination, and GE's famed FastWorks methodology, she helped to turn a process-heavy, risk-averse culture, to one that increasingly embraced transparency, adaptability, iteration, and discovery. She shows how each one of us can -- in fact, must -- become a "change maker"--an instigator of change -by giving ourselves permission to imagine a better way. For Comstock, the concept of being "change ready" calls for the courage to defy convention, the resilience to overcome doubts, and the savvy to know when to go around corporate gatekeepers to reinvent what is possible. It means being willing to move forward without having all the answers, while recognizing that inevitably there will be tension and conflict. It requires an uncompromising faith in experimentation, and a belief that disruption is something you engage, not simply respond to. Among the practical takeaways Comstock offers in Imagine It Forward: ·Give yourself permission. Every change maker must learn to give herself permission to push outside expectations and boundaries. ·The power of discovery. Discovery is the process of bringing the outside into your organization. It is about infusing yourself and your team with a spirit of inquiry and curiosity, turning the world into a classroom. ·Find a "Spark.' Bring in provocateurs to challenge established ways of thinking; they can be a powerful catalyst for change. ·Story Craft. Strategy is a story well told. To innovate successfully, you have to craft a new narrative about what the organization stands for in order to change how people think and act. "Ideas are rarely the problem," writes Comstock. "What holds all of us back, really--is fear. It's the attachment to the old, to 'What We Know.'" Confronting today's accelerating change requires an extraordinary degree of problem-solving, collaboration, and forward-thinking leadership to unlock everyone's potential. Imagine It Forward masterfully points the way"--